Território e desigualdades socioespaciais: uma análise acerca das dinâmicas urbanas na cidade de Barcarena-PA - MENEZES, Paula Beatriz Rêgo (2022)
The territories of Brazilian and Amazonian cities have been undergoing accelerated transformations in the last two decades of the 21st century, as a result of the incorporation of these territories in the context of globalization of capital. On the scale of the city of Barcarena, a rapid process of industrialization and urban expansion was evidenced, facts that have caused the advancement of new economic agents, high demographic growth in addition to the expansion and socio-spatial inequalities in the territories of that city, evidenced by the reduced access to land, urban infrastructure and services. Therefore, aim at to analyze the demographic dynamics, urban expansion and uses of the territory of Barcarena from the 2000s onwards. The method used was historical-dialectical materialism. As methodological procedures, it was based on surveys and document analyses. The research was also made up of photographic records, cartographic production and semi-structured interviews with public agents, private and representatives of local communities. Finally, the results obtained by the present research reveal that Barcarena-Pa despite the accelerated urban growth still constitutes intense urban-rural relations, the constant transformations potentiated by the industry, conceived an uneven geographic development, with expressive manifestations in the uses and against uses of the territory.